2004
DOI: 10.1097/01.ta.0000108630.34225.85
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgery for Thoracolumbar Spine Injuries Decreases Complications

Abstract: Early surgery in severely injured patients with thoracolumbar spine trauma was associated with fewer complications and shorter hospital and intensive care unit lengths of stay, required less ventilator support for noninfectious reasons, and did not increase neurologic deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 13 publications
(19 reference statements)
3
69
2
2
Order By: Relevance
“…There is consensus that nonneurological outcome measures such as hospital and ICU length of stay (LOS), duration of mechanical ventilation, and pneumonia and other complications improve in patients undergoing early surgical stabilization 13,16 -more markedly in patients with polytrauma and thoracic injuries. 13 Whether early surgical intervention improves neurological outcomes is less clear.…”
Section: Surgical Timingmentioning
confidence: 99%
“…There is consensus that nonneurological outcome measures such as hospital and ICU length of stay (LOS), duration of mechanical ventilation, and pneumonia and other complications improve in patients undergoing early surgical stabilization 13,16 -more markedly in patients with polytrauma and thoracic injuries. 13 Whether early surgical intervention improves neurological outcomes is less clear.…”
Section: Surgical Timingmentioning
confidence: 99%
“…Advantages of early femur fracture fixation are well known and reported by several studies [5,6,10,20,24,40,47]. Clinical research in the past decade suggests that early stabilization of spinal fractures may improve neurological outcome, reduce complications, ICU and hospital stay [8,10,11,19,26,30,32,36,41,45,49]. Early stabilization is considered safe but a recent study by Kerwin et al [26] reports a trend to higher mortality in early-operated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Early surgical decompression was associated with a shorter hospital length of stay in eight studies [7,14,16,27,32,37,40,42] (although Guest et al [27] reported no p values), whereas the other only recorded the length of stay in the ICU [52]. A subset of these studies further divided overall length of stay with the duration of stay in the ICU [14,16,27,32] and found this time point was also less in patients receiving early decompressive surgery. Only one study [32] that measured these values found no correlation between timing of surgical decompression and the length of stay in the ICU.…”
Section: Histopathologic Correlationmentioning
confidence: 99%
“…Four studies [7,36,37,41] reported no difference in the rate of medical complications between the early and late surgical groups, whereas four studies found overall fewer complications in the persons receiving early surgical decompression. Specifically, Mirza et al [42] reported fewer complications in persons receiving surgery within 72 hours of injury; Croce et al [16] reported lower rates of pneumonia and DVT in persons receiving surgery within 24 hours; Chipman et al [14] reported a lower frequency of all complications in patients with an Injury Severity Score (ISS) greater than 15 and receiving surgery within 72 hours of injury (although this same group reports equal medical complications in persons with low ISS [less than 15] regardless of the time of decompression); McKinley et al [40] report higher rates of pneumonia in the late surgery group but equal rates of other complications (DVT, pulmonary embolism, ulcers).…”
Section: Histopathologic Correlationmentioning
confidence: 99%
See 1 more Smart Citation